System hydrodynamics to reduce fouling of air-sparged immersed flat-sheet microfiltration membranes - Hamann, Martin Louis (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2010.